2007
DOI: 10.1080/15368370701410558
|View full text |Cite
|
Sign up to set email alerts
|

The Urban Decline of the House Sparrow (Passer domesticus): A Possible Link with Electromagnetic Radiation

Abstract: During recent decades, there has been a marked decline of the house sparrow (Passer domesticus) population in the United Kingdom and in several western European countries. The aims of this study were to determine whether the population is also declining in Spain and to evaluate the hypothesis that electromagnetic radiation (microwaves) from phone antennae is correlated with the decline in the sparrow population. Between October 2002 and May 2006, point transect sampling was performed at 30 points during 40 vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 28 publications
1
60
0
1
Order By: Relevance
“…For instance, its populations have experienced considerable declines since the replacement of horses by cars in the 1920s, followed by nonurban population declines associated with the reduced availability of both grain and invertebrates due to the industrialization of farmland practices, e.g., heavier use of pesticides and herbicides, reduced grain spillage, improved grain storage, from the 1980s onward (Summers-Smith 2003). The renewed decline of its urban populations since the 1990s has been much more complex and highly variable with the reduced number of shrubs and nesting sites, increased pesticides use in greenspaces, and increased concentration of lower socioeconomic status areas all being related to lower sparrow numbers (Summers-Smith 2003, Balmori and Hallberg 2007, Shaw et al 2008, Murgui and Macías 2010, García-Rodríguez 2011. However, it is unclear which of these reasons are directly causing the decline (De Laet and Summers-Smith 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, its populations have experienced considerable declines since the replacement of horses by cars in the 1920s, followed by nonurban population declines associated with the reduced availability of both grain and invertebrates due to the industrialization of farmland practices, e.g., heavier use of pesticides and herbicides, reduced grain spillage, improved grain storage, from the 1980s onward (Summers-Smith 2003). The renewed decline of its urban populations since the 1990s has been much more complex and highly variable with the reduced number of shrubs and nesting sites, increased pesticides use in greenspaces, and increased concentration of lower socioeconomic status areas all being related to lower sparrow numbers (Summers-Smith 2003, Balmori and Hallberg 2007, Shaw et al 2008, Murgui and Macías 2010, García-Rodríguez 2011. However, it is unclear which of these reasons are directly causing the decline (De Laet and Summers-Smith 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However previous studies results showed agricultural area provides plenty of food in the form of food grains and insects (Balmori and Hallberg, 2007). The main reason for abundance of House sparrow in the beach area mainly on account of availability food resource by the way of fallen grains and other food stuffs present in shops.…”
Section: Observations and Conclusionmentioning
confidence: 94%
“…It is reported that the once widely distributed species in most parts of Europe and Asia is slowly disappearing from urban areas (Gulati 2005 . Predation from the domesticated and wild cats (Felis catus, Carnivora: Felidae) and sparrow hawks (Accipiter nisus, Accipitriformes: Accipitridae), and the electromagnetic radiation from cell-phone towers are considered as reasons for their decline (Balmori & Hallberg, 2007). Passer domesticus populations are vanishing from different metropolises and in newly developing urban areas .…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…Mobile phone tower radiation:-Electromagnetic radiation from cell phone towers is also one other reason for the decline of sparrow population (Balmori & Hallberg 2007). However, experimental studies involving ex-situ simulations of different strengths of electro-magnetic radiations in Europe have yielded mixed results on their impacts on reproduction of birds, and no conclusive evidence has been produced so far.…”
Section: Impact Of Predators:-mentioning
confidence: 99%